An electrochemical immunosensor coupling a bamboo-like carbon nanostructure substrate with toluidine blue-functionalized Cu(ii)-MOFs as signal probes for a C-reactive protein assay. Issue 12 (10th February 2021) - Li, Mei; Xia, Xiaojuan; Meng, Shuang; Ma, YuChan; Yang, Tong; Yang, Yunhui; Hu, Rong
Abstract : A sandwich immunosensor based on a toluidine blue (Tb) loaded metal organic framework (Cu(ii )-HKUST-1/Tb) as the signal label and a nitrogen-doped 3D carbon nanostructure as the immobilizing matrix was constructed for the detection of C-reactive protein. Abstract : In this paper, a novel sandwich immunosensor based on a toluidine blue (Tb) loaded metal organic framework (Cu(ii )-HKUST-1/Tb) as the signal element and a nitrogen-doped 3D carbon nanostructure as the electrode substrate was constructed for the detection of C-reactive protein (CRP). Tb as an electrochemically active agent usually forms a polymer by aggregation in the solvent, causing a poor electrochemical response. Therefore, in order to overcome this obstacle, Cu(ii )-HKUST-1 with a porous nanostructure and large specific surface area as a carrier could adsorb a large number of Tb molecules on its surface to improve its electrochemical performance. In addition, the high electron transfer efficiency of the N-doped bamboo-like carbon nanotubes (CoFe/N-GCT) improves the sensitivity of the biosensor. Differential pulse voltammetry (DPV) was used to detect the current signal of Tb at −0.2 V. The current response increased with the increase in concentration of CRP, ranging from 0.5 to 200 ng mL −1 . The detection limit is 166.7 pg mL −1 (S/N = 3). Moreover, the proposed biosensor can be applied in real serum sample detection. It has potential applications in the field of biomedicine assays.